Comparison of particle size analysis of ground grain with, or without, the use of a flow agent - Diederich, W.; Goodband, Robert D.; Tokach, Michael D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
The American Society of Biological and Agricultural Engineers’ standard for particle size analysis indicates that the analysis can be conducted with or without the use of a flow agent. Because of this allowed variation in procedures, particle size analysis results can be variable and difficult to interpret, depending on whether the laboratory uses a flow agent or not. Therefore, a retrospective analysis was made of 603 samples of ground corn analyzed for particle size with, or without, 0.5 g of synthetic amorphous precipitated silica (Sipernat® 22-S) per 100 g of sample. Results of both analyses were compared with a Method of Agreement analysis. Results indicated that there was a bias between the two procedures for particle size analysis, but that the bias was consistent across the range of particle sizes evaluated(400 to 1000 μ). Particle size analysis conducted with a flow agent will result in a mean particle size that is approximately 80 μ smaller than the result from analysis without a flow agent. The same procedures were used in comparison of particle size standard deviation. Using a flow agent produced a greater particle size standard deviation value than without a flow agent. Unlike the bias for the particle size analysis, which was consistent for the wide range of samples evaluated, the standard deviation values showed a significant bias. As the standard deviation of the sample increased, the magnitude of difference between the two procedures also became greater. Results of this study indicate that there are differences in results between the two procedures; therefore, selection of one of the two procedures as the official standard is necessary. Also, it is important to know if a flow agent was, or was not, used in the analysis when interpreting results.
Keywords: Swine; Flow agent; Particle size; Quality control